Sodna presoja denarnih odločitev v pravu Evropske unije - Zagradišnik, Renata (Podjetje in delo, 2014)
Author holds that the link of the European Union to the rule of law is shown through the submission of all its activity to the judicial scrutiny by the European Court of Justice. Same is true for monetary policy decision adopted by the European Central Bank (ECB). The judicial review is the sole mechanism for accountability of a central bank who was established as an independent institution in order to maintain the price stability and who is outside the scope of traditional system of checks and balances and therefore not under the control by the parliament and government (or in the case of the ECB under control by the Council, Commission and European Parliament). The effectiveness of the judicial review depends on its scope, therefore the author analyses the factors that impact the scope of judicial review. Furthermore she analyses possible judicial review of measures adopted in core fields of ECB's monetary competences. On this basis she tries to determine the effectiveness of judicial control of monetary decisions and its impact on the central bank independence.
Keywords: European Union; Evropska centralna banka; Evropska unija; monetarne unije; odločanje; pravna ureditev